Asthma Control Level and Relating Socio-Demographic Factors in Hospital Admissions - Yalçınkaya, Gönül; Kılıç, Mahmut (International Journal of Statistics in Medical Research, 2022)
Purpose: Asthma is one of the serious public health problems that we face today and the rate of complete control is very low. This study aims to determine the level of asthma control and its relationship with socio-demographic factors in asthma patients. Methods: This cross-sectional study was conducted between November 2020-April 2021 among people aged 18-64 who applied to the hospital and were not diagnosed with asthma. The data of the research were made with the personal information form, ACT (asthma control test). ACT is a questionnaire consisting of 5 questions. Patients rate each question between one and five points. The total score of the five questions forms the test result. If the total score is 25, it is considered as full control, 24-20 as partial control, and ≤19 as not under control. In the research, 206 people participated. Results: Of the participants, 60.7% were female, 60.2% had a family history of asthma, 94.2% of them used asthma medication, and the average age was 45.7±13.85. In the last 12 years, 50.5% of asthma patients stated that they applied to the emergency department due to respiratory problems, and 23.3% were hospitalized due to these problems. It was determined that 78.6% of asthma patients were not under control, 21.4% were under partial control, and there was no patient under full control. The mean age (48.8) and body mass index (BMI) (29.4) of those whose asthma was not under control were higher than those with partial control (32.2 and 24.7, respectively) (p<0.001). It has been determined that the probability of asthma not being controlled increases as age and BMI increase, and life satisfaction decreases, and it is higher in quit smokers than in current smokers (p<0.05). Conclusion: Asthma is largely uncontrolled. The rate of uncontrolled asthma increases with increasing age and BMI. Patients with high BMI should be supported to lose weight and should be directed to exercise.